The role of open streets Cape Town street events in shaping everyday mobility in Salt River and Observatory : towards bridging mobile, spatial and social divide - Taylor, Frances Jessica (Department of Environmental and Geographical Science, 2016)
This study interrogates the role of Open Streets Cape Town's day-long street events in disrupting complex systems and hierarchies of everyday street mobility that maintain the mobile, spatial and social divides of Cape Town. The test was whether OSCT events 1) bridged the mobile divide by replacing car-dominated streets with people-centred public space; 2) bridged the spatial divide by bringing fluidity to the mobility of people between usually isolated public spaces; and 3) bridged the social divide by replacing practices of avoidance and exclusion with an everyday cosmopolitan sensibility. The investigation used mobile methodologies and an embedded approach. OSCT proved to be successful at bridging the mobile divide by creating a shared public space, but had mixed success with bridging spatial and social divides. A greater sensitivity to how existing social and spatial divides can be reproduced during events would improve this. Sager's (2006) freedom of mobility framework was reworked and proved to be useful in monitoring individuals situated differently in the shifting complex of power, identity and everyday life across a changing motilities landscape. The underlying mobility framework revealed a need for developing better street navigation skills to create robust and equitable freedom of mobility for street users, necessary for independence from mediators such as cars, private street security and prejudice ideas about people and places that perpetuate division. OSCT events are useful in opening up people's eyes to what could be, but the value is diminished if there are no ongoing interventions sustaining this new understanding. Interventions that tackle the everyday systems supporting the divisions are needed to supplement the interventions of OSCT events. This will add substance between events and enhance the value of the events themselves.